The effect of teacher's presence at children's bedside on the anxiety of mothers with hospitalized children: A randomized clinical trial - Tayebeh Reyhani; Seyedeh Zahra Aemmi; Amir Emami Zeydi (Wolters Kluwer Medknow Publications, 2016)
Background: The hospitalization of a child is a stressful experience for parents, especially mothers. Not having access to the teacher and not being able to continue school studies within the hospital by hospitalized children is a common reason for anxiety in them and their parents. The current study aimed to determine the effect of teacher's presence at children's bedside on the anxiety of mothers with hospitalized children. Materials and Methods: In a randomized clinical trial, a total of 50 mothers with children admitted to pediatric ward of one teaching hospital in Mashhad, Iran, were randomly allocated to two equal groups. In the intervention group, the teacher was present at children's bedside for daily education and practices, but the control group received standard routine care. The mothers' level of anxiety was evaluated using the Spielberger State-Trait Anxiety Inventory, which was completed at both admission and prior to child's discharge. Data were analyzed using SPSS. Results: The results showed that before intervention, the means and standard deviations of the mothers' trait anxiety scores in the experimental and control groups were not significantly different (P = 0.164). However, after intervention, the mothers' mean trait anxiety scores decreased significantly in the intervention group compared to the control group (P < 0.001) and compared to the pre-intervention phase (P < 0.001). Conclusions: It seems that the presence of a teacher at children's bedside is an easy and effective strategy to reduce anxiety in mothers regarding their children hospitalization.